THE ANALYSIS OF PROGRAM IMPLEMENTATION INSTITUTIONAL ENTREPRENEUR COMMUNITY TANGAN DI ATAS (TDA) AGAINST INCREASED REVENUE LOCAL ECONOMY IN MEDAN - Putra, Umar Maya (Universitas Negeri Medan, 2019)
This study aims to analyze the Program of Institutional Entrepreneur Community Tangan Di Atas (TDA) Against Increased Revenue Local Economy in Medan. The problem in this research is to see the extent to which the opportunities of independent variables such as entrepreneurship education, capital, selling price, the amount of labor, marketing through the exhibition of entrepreneurship of the dependent variable is the income of Small Enterprises assisted Institutional Tangan Di Atas (TDA) of Medan. The data used is primary data with the primary form of questionnaires to the small enterprises patronage of TDA Medan with observation period in 2013 s.d. 2015. While the methods of analysis used for primary data is Probit with analysis software program E Views 6 and secondary data obtained on a general overview of the small enterprises patronage of TDA Medan and the results of the study of literature (Library Research) to support his theories relevant to the research. From the results of this study indicate that there is a positive correlation and significant between entrepreneurship education, capital, selling price, the amount of labor and marketing aspects through the exhibition of entrepreneurship opportunity of increased revenue Small Enterprises Patronage TDA Medan otherwise there is a positive relationship and not significant among the workforce to an increased chance the small enterprises patronage ofÂ TDA revenue Medan. TDA Medan can be able to focus in increasing entrepreneurship education, marketing aspects through the exhibition of entrepreneurship, product selling prices, capital and to concentrate in the amount of labor professionally to get the result maximallyÂ to an increased chance the small enterprises patronage ofÂ TDA revenue Medan.